An Approach to the Prevailing Conceptions in the Statistical Training of Health Professionals - Vicente Eloy Fardales Macías; Raquel Diéguez Batista; Arturo Puga García (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2014)
Background: deficiencies in the statistical training of health professionals prevail and there are claims for focusing it towards a greater relation with medical practice. Objective: to characterize statistical training process of health professionals. Methods: an exploratory study was conducted in the medical university of Sancti Spiritus. Surveys were applied to thirty professors selected by stratified sampling in order to obtain evidence on the how statistics is conceived according to the following conceptions: statistics as a resource for biomedical research, as a resource that supports medical practice and as a resource to solve problems in pre-professional medical practice. Results: Eighty percent of the surveyed professors rated their statistical training as insufficient; 66% reported promoting statistics as a tool for biomedical research; and 80% stated that they encourage student research as an essential means for applying statistical contents in medical undergraduate studies. Conclusions: statistics is conceived as a mere resource for biomedical research, to detriment of its use as a resource that supports medical practice. There are deficiencies in the theoretical and practical conception related to the application of statistics during training of health professionals.